Neuroendocrine differentiation in basal cell carcinoma. Issue 5 (3rd September 2017) - Houcine, Yoldez; Chelly, Ines; Zehani, Alia; Belhaj Kacem, Linda; Azzouz, Haifa; Rekik, Wafa; C., Hend; Haouet, Slim; Kchir, Nidhameddine
ABSTRACT: Basal cell carcinoma (BCC) is the prototypical basaloid tumor of the skin. It may show various patterns simulating other cutaneous tumors due to its pleomorphism. It may have an unusal pattern of differentiation such as squamous, sebaceous, apocrine, eccrine, pilar, and endocrine differentiation. In order to establish the relative frequency of neuroendocrine differentiation in BCC, we performed a retrospective study of 33 consecutive BCCs using conventional immunohistochemistry with two neuroendocrine antibodies: Chromogranine A and synaptophysine. The age of the patients ranged from 17–83 years with mean of 65 years. The male to female ratio was 16:17. In immunohistochimestry, Chromogranine A was seen in 72.2% (24/33) while Synaptophysine was positive in 9.09% (3/33). Their expression was cytoplasmic and membranous and was seen in the periphery of these tumors in the overlying cells. Positive staining of chromogranine A was high (75–100% of tumors cells) in 9%, intermediate (25–75% of tumors cells) in 33% of cases and relatively low (<25%) in 30.3% of cases.